Estudo do extrato de Bauhinia forficata L. sobre o diabete em ratas prenhes - Volpato, Gustavo Tadeu [UNESP]; Damasceno, Débora Cristina [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (My University, 1999)
The objective of this paper was to study the aqueous extract of Bauhinia forficata L. (pata-de-vaca) effects on streptozotocin-induced diabete pregnant rats. We used Wistar pregnant rats, dividided in 3 experimental groups: control (C, n=7), non-treated diabetics (DNT, n=7) and streptozotocin induced-diabetics treated with an aqueous extract of pata-de-vaca leaves, 200 mg/kg dose (DT, n=7). The animals received the extract through a gastric tube (gavage). The blood glucose level were verified on day 0, 5, 14 and 20 of pregnancy. During pregnancy, the daily mean water intake, food intake and average maternal weight gains of rats were measured. The results demonstrated that plant extract reduced the postimplantation loss porcentage, increasing the number of live fetuses likely to the control group. We found increased food and water intake of the DT and DNT pregnant rats compared to control due to hyperglycemic state. We also observed average maternal weight gains was likely to the DT and control groups on different pregnant periods, suggesting treatment with the plant contributed for the rat weight gains. The blood glucose level of dams did not present significative differences between DT and DNT groups. Thus, the B. forficata aqueous extract, 200 mg/kg dose, did not present hypoglycemic effect on streptozotocin-induced diabete pregnant rats. Nevertheless, the results suggest that DT pregnant rats were kept safe the for B. forficata aqueous extract, allowing at term pregnant occurence.
Study of Bauhinia forficata L. extract on diabete in pregnant rats
Keywords: Bauhinia forficata; Diabetic rats; Hypoglycemic; Medicinal plant; Pata-de-vaca; Streptozotocin; bauhinia forticata extract; glucose; plant extract; unclassified drug; animal experiment; aqueous solution; controlled study; drug effect; feeding; female; fluid intake; food intake; glucose blood level; hyperglycemia; hypoglycemia; nonhuman; pregnancy; rat; streptozocin diabetes